Acne scar and scar synthesis system using height map and improved subsurface scattering color model. (16th December 2016) - Choi, Taeyoung; Chin, Seongah
Abstract: Recently, people have paid more attention to skin that seems determine age, beauty and appearance. In particular, acne scar that tends to grow in young generation. Synthetic model can help to prevent them to care beforehand. This study proposes a representation for acne scars and general scars using a height map and an improved subsurface scattering color model. In consideration of the geometric properties of acne scars classified into ice pick, rolling and boxcar, a height map is used. Where the improved subsurface scattering color model and shading are applied, convenient system interfaces are provided to represent wounds and scars conveniently. An automation function is added for the user to control the height map, as well as four shading functions comparable with the shading function proposed in this study. In addition, a user study is performed to validate the proposed method.